The Covenant in Zacharias Ursinus - Visser, Derk (The sixteenth century journal, 1987)
After a summary of the three main historical approaches to recent works on the covenant in Protestant theology, the article focuses on the allegation that Zacharias Ursinus's Major Catechism, composed in 1561-62 (but not published until after his death, in 1584), laid the basis for subsequent developments of the covenant of works doctrine. The article suggests that the doctrine does not occur in the works Ursinus published himself; appeared too quickly after his death to be based on the one phrase in the Major, and that the origin of the doctrine should be sought in the writings concerned with pastoral cares concerning the proper celebration of the sabbath.